Implementation of a Z-matrix approach within the SIESTA periodic boudnary conditions code and its application to surface adsorption - Hoft, R.; Gale, Julian; Ford, M. (Taylor & Francis Ltd, 2006)
We implement a flexible Z-matrix approach in the density functional theory (DFT) periodic boundary conditions code, SIESTA. This allows a mixture of Z-matrix and Cartesian coordinates to be used for geometry specification and optimisation. In addition, geometry constraints in the form of fixed coordinates and fixed linear relationships between coordinates can be specified. A Z-matrix approach in condensed phase calculations can be advantageous, for example in studying molecular adsorption onto a surface, both in terms of flexibility and efficiency.We demonstrate our implementation for the case of thiol adsorption on the Au(111) surface.